Letter from Paul E. Wolven to the Ventura County Board of Supervisors - Paul E. Wolven:::::: (1971)
Letter from City Manager Paul E. Wolven to the Ventura County Board of Supervisors discussing the rejected agreement and desires to continue negotiating an agreement for the former Oxnard Air Force Base.